2015
DOI: 10.1016/j.jhep.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and senescence in fibrosing cholangiopathies

Abstract: Fibrosing cholangiopathy such as primary sclerosing cholangitis (PSC) and biliary atresia (BA) is characterized by biliary epithelial injuries and concentric fibrous obliteration of the biliary tree together with inflammatory cell infiltration. In these diseases, inappropriate innate immunity is reported to contribute more to bile duct pathology as compared with various aspects of "classical" autoimmune diseases. Primary biliary cirrhosis (PBC) is characterized by chronic cholangitis with bile duct loss and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 137 publications
3
64
0
Order By: Relevance
“…Senescent biliary epithelial cells may modulate the microenvironment surrounding bile ducts by expressing senescence -associated secretory phenotypes (SASP) and contribute to maintaining inflammation and fibrosis around bile duct lesions in PBC. Deregulated autophagy followed by cellular senescence in biliary epithelial cells may be closely related to the abnormal expression of mitochondrial antigens and subsequent autoimmune pathogenesis in PBC (47,48). The biliary epithelial cells of PBC are exposed to excessive oxidative stress because of a decrease in their anti-oxidative abilities (49).…”
Section: The Journal Of Medical Investigation Vol 64 February 2017mentioning
confidence: 99%
“…Senescent biliary epithelial cells may modulate the microenvironment surrounding bile ducts by expressing senescence -associated secretory phenotypes (SASP) and contribute to maintaining inflammation and fibrosis around bile duct lesions in PBC. Deregulated autophagy followed by cellular senescence in biliary epithelial cells may be closely related to the abnormal expression of mitochondrial antigens and subsequent autoimmune pathogenesis in PBC (47,48). The biliary epithelial cells of PBC are exposed to excessive oxidative stress because of a decrease in their anti-oxidative abilities (49).…”
Section: The Journal Of Medical Investigation Vol 64 February 2017mentioning
confidence: 99%
“…Cholangiocytes are injured by various stresses including hydrophobic bile acids such as glycochenodeoxycholic acid (GCDC) in cholangiopathies [1,2] . Impaired 'biliary HCO 3 -umbrella,' which is important to protect biliary physiology, may be a common pathological condition in primary biliary cholangitis (PBC) and other cholangiopathies [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Although these cells are metabolically still active, this process is followed by eventual loss of affected cells. Recent studies showed that cellular senescence was implicated in several biliary diseases and also premature or stress-induced senescence was discussed with respect to senescence-associated secretory phenotype (SASP) which is associated with microenvironments of affected cells or tissues [11,12]. Interestingly, Sasaki et al reported that bile ductules showed cellular senescence in PBC, and that sustained cellular senescence might lead to the eventual loss of bile ductules and CoH loss [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Sasaki et al reported that bile ductules showed cellular senescence in PBC, and that sustained cellular senescence might lead to the eventual loss of bile ductules and CoH loss [9,10]. It is, moreover, reported that senescence is propagated through positive feedback by nearby senescent cells, causing senescence of adjacent bile ductules and CoH in PBC [11,12]. Recently, we have reported that cellular senescence may play an important role in the pathogenesis of fibrosing cholangiopathies including PBC, and senescence of biliary epithelial cells may be induced by several senescent stimuli, particularly impaired autophagy and oxidative stresses [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation